2015
DOI: 10.4081/gh.2015.307
|View full text |Cite
|
Sign up to set email alerts
|

Estimating population and livestock density of mobile pastoralists and sedentary settlements in the south-eastern Lake Chad area

Abstract: Mobile pastoralists provide major contributions to the gross domestic product in Chad, but little information is available regarding their demography. The Lake Chad area population is increasing, resulting in competition for scarce land and water resources. For the first time, the density of people and animals from mobile and sedentary populations was assessed using randomly defined sampling areas. Four sampling rounds were conducted over two years in the same areas to show population density dynamics. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…We were surprised that the prevalence of F. gigantica infection at followup was slightly higher than at baseline, and indeed, 6-month post-treatment egg shedding was above the baseline level. These observations might be explained, at least partially, due to suspected high pasture and water point contamination, resulting from high livestock numbers on the shores of Lake Chad towards the end of the dry season, prior to moving out of the Lake Chad wetlands (Jean-Richard et al, 2015). Our results are not conclusive whether re-infection occurred still in the Lake Chad area or during migration outside the wetlands.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…We were surprised that the prevalence of F. gigantica infection at followup was slightly higher than at baseline, and indeed, 6-month post-treatment egg shedding was above the baseline level. These observations might be explained, at least partially, due to suspected high pasture and water point contamination, resulting from high livestock numbers on the shores of Lake Chad towards the end of the dry season, prior to moving out of the Lake Chad wetlands (Jean-Richard et al, 2015). Our results are not conclusive whether re-infection occurred still in the Lake Chad area or during migration outside the wetlands.…”
Section: Discussioncontrasting
confidence: 64%
“…The regions are located in the Sahelian ecological zone with borders to Cameroon, Niger and Nigeria in the West. The area is inhabited by fishermen, a sedentary population that predominantly lives of agriculture, and different ethnic groups of mobile pastoralists with large numbers of livestock (Jean-Richard et al, 2015). Participating animals originated from herds owned by one of the four predominant ethnic groups of mobile pastoralists: (i) Arabs; (ii) Buduma; (iii) Fulani; and (iv) Gorane.…”
Section: Study Area and Local Husbandry Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the period of pastoralism, humans were clustered 50 times more than Hunter-Gatherers, and, when traditional farming was developed, clustering increased respectively (Table 1). At the same time, energy required per ha was ~100 and ~200 times more (Figure 9) [75,76,[79][80][81][82][83][84][85][86][87]. Sackett found that adults in foraging and horticultural societies work, on average, about 6.5 h a day, whereas people in agricultural societies work on average 8.8 h a day [88].…”
Section: Prehistorc Societiesmentioning
confidence: 99%
“…Prehistoric human, different types of living, minimum area, and energy needs for food production (present data as order of magnitude)[75,76,[79][80][81][82][83][84][85][86][87]. Prehistoric human, different types of living, minimum area, and energy needs for food production (present data as order of magnitude)[75,76,[79][80][81][82][83][84][85][86][87].…”
mentioning
confidence: 99%